Feasibility of Android-Based Application SCIQU (Science in Al-Quran) as Science Learning Media for Madrasah Ibtidaiyah (MI) - Muttakin Muttakin; Zainul Mujtahid; Amam Taufiq Hidayat; Munzir Absa; Thalitha Attahara; Rahmah Nursada (Jurnal Penelitian Pendidikan IPA, 2023)
In this age of technological advancement, the process of learning in the classroom is required to be more adaptive, using various media that can enhance it. One of the learning media that can increase studentâ€™s interest is picture story media (comics). In this study, an android-based comic media was developed, called Science in Al-Qur'an (SCIQU), with material about clean and healthy lifestyles for grade V Madrasah Ibtidaiyah (MI) students. The media was developed using Research and Development (R & D) Method with ADDIE (Analyze, Design, Develop, Implement, Evaluate) Model. Â The media developed and the material presented in the media were validated by media expert validators and material experts. From the validation results, it was found that the media developed fell into the "Very Feasible" category with a total validity value of 95.34%. Likewise, the material presented in the SCIQU comic media is included in the "Very Feasible" category with a total validity value of 96.48%. So the SCIQU comic media that has been developed can be said to be very feasible to be implemented to MI students across the country.